Lifestyle and impact on cardiovascular risk factor control in coronary patients across 27 countries: Results from the European Society of Cardiology ESC-EORP EUROASPIRE V registry. (29th August 2020) - Kotseva, Kornelia; De Backer, Guy; De Bacquer, Dirk; Rydén, Lars; Hoes, Arno; Grobbee, Diederick; Maggioni, Aldo; Marques-Vidal, Pedro; Jennings, Catriona; Abreu, Ana; Aguiar, Carlos; Badariene, Jolita; et al.
Abstract: Aims: The aim of this study was to determine whether the Joint European Societies guidelines on secondary cardiovascular prevention are followed in everyday practice. Design: A cross-sectional ESC-EORP survey (EUROASPIRE V) at 131 centres in 81 regions in 27 countries. Methods: Patients (<80 years old) with verified coronary artery events or interventions were interviewed and examined ≥6 months later. Results: A total of 8261 patients (females 26%) were interviewed. Nineteen per cent smoked and 55% of them were persistent smokers, 38% were obese (body mass index ≥30 kg/m 2 ), 59% were centrally obese (waist circumference: men ≥102 cm; women ≥88 cm) while 66% were physically active <30 min 5 times/week. Forty-two per cent had a blood pressure ≥140/90 mmHg (≥140/85 if diabetic), 71% had low-density lipoprotein cholesterol ≥1.8 mmol/L (≥70 mg/dL) and 29% reported having diabetes. Cardioprotective medication was: anti-platelets 93%, beta-blockers 81%, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers 75% and statins 80%. Conclusion: A large majority of coronary patients have unhealthy lifestyles in terms of smoking, diet and sedentary behaviour, which adversely impacts major cardiovascular risk factors. A majority did not achieve their blood pressure, low-density lipoprotein cholesterol and glucose targets. Cardiovascular prevention requires modern preventive cardiology programmes delivered by interdisciplinary teams of healthcare professionals addressing all aspects of lifestyle and risk factor management, in order to reduce the risk of recurrent cardiovascular events.